THE EVALUATION OF THE PRESENT FRENCH TEXTBOOK USED IN SENIOR HIGH SCHOOLS IN SEMARANG AND ITS SURROUNDINGS - Urip, Sri Rejeki; SuÃƒÂ¢Ã¢Â‚Â¬Ã¢Â„Â¢udi, Astini; Saleh, Mursid (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2011)
School Based Curriculum (SBC) as one of the decentralization in education authorizesteachers to develop their own teaching materials. The fact shows that the teacher is stillminimal in writing, including writing textbooks. To facilitate French teachers in writing a Frenchtextbook, a guideline is needed. In Exploration Phase of Research and Development , one ofthe objectives is to find out the quality of French textbook used today. Knowing its strengthsand weaknesses is useful because the information can be used as data for developing aguideline for writing a better French textbook. To collect the data, the methods used were(1) Document Analysis, (2) In-depth interviews, (3) Questionnaires, and (4) Focus GroupDiscussion. To analyze the data, the Constant Comparative Method was utilized. For thetrustworthiness of the data, Triangulation, Member-checking were applied. By using theFrench textbook evaluation instrument set by BSNP and equipped with Cunningsworthcriteria, the six volumes of Bonjour Chers Amis were evaluated. There are four components tobe evaluated: Feasibility of Contents, Feasibility of Presentation, Feasibility of Language, andPractical considerations. The findings reveal that the criteria of French textbook evaluation ofBSNP has not been implemented optimally. These findings provide the information of thequality of the French textbook currently used in Semarang and its surroundings. Theinformation can be used as an overview what things are to be followed and avoided indeveloping a guideline for writing a French textbook integrating SBC and CEFRL.